Effect of iron (III) oxide concentration on the performance of meta-resonators embedded in cementitious matrix - Sum, Yee Loon (2022)
Efforts are currently underway to improve the performance of small electric antennas and resonator-based antennas embedded in the civil infrastructure. One of the main limitations of these small antennas is that they have narrow bandwidths which limit their use when embedded in concrete. The present work shows that by changing the amount of iron (III) oxide microparticles in a cementitious matrix, not only does the impedance matching of the embedded array improve by as much as 20 dB, it also produces a lesser shift in resonant frequency (RF) than the original cementitious matrix alone. Further analysis of antenna transmission coefficient S21 values shows that adding 4% iron (III) oxide into cement paste improves the RF power transmission into the material compared to the control by as much as 10 dB. Given that iron (III) oxide microparticles are easily available as admixture pigments for coloring mortar or concrete, it is possible to fast track implementation of this application in new construction.